PERAN ETHICAL HACKING DALAM MEMERANGI CYBERTHREATS - Qorry Aina Fitroh; Bambang Sugiantoro (LPPM Universitas Putera Batam, 2023)
The efforts to digitize and optimize various things in the modern world will certainly highlight issues related to cybersecurity such as data breaches, security breaches, and so on. Ethical hacking and its need in the future cannot be avoided. Ethical hacking technology is spreading in almost every aspect of life, especially the computer industry, which requires protection of important data and must be handled with the right technology. Ethical hacking aims to find vulnerabilities in security systems and discover potential data breaches. This contrasts with the common understanding of hacking, which is black hat hackers who damage systems with malicious intent and steal data and infect viruses. Ethical hacking is a way to combat and neutralize black hat hackers. Teaching ethical hacking is preparing professionals in the information security field with the tools and skills to combat and prevent cybersecurity threats. Teaching inexperienced people in information security with aggressive methods can be viewed as both beneficial and harmful. This is because the same methods are used by malicious hackers hence educating professionals in information security may be perceived as enhancing malicious hackers. Using the literature study method, this article discusses various issues related to ethical hacking.